Developing a Written Descriptive Text through Interactive Multimedia - Rohadi, Adip; Aimah, Siti; Mulyadi, Dodi (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
Most of English teachers still used the conventional teaching and only used PowerPoint presentation during the teaching process. Actually, teachers can use the more attractive media such interactive CD. This study was aimed to find out the effectiveness of developed interactive CD in teaching written descriptive text and the studentsâ response toward the developed interactive multimedia. This research used research and development method from Sugiyono (2009, p. 289). The data taken were the media assessment data by the experts, questionnaire about studentsâ response to the interactive CD, and effectiveness of interactive CD analysis. The expertsâ assessment results showed that the interactive CD was scored 94% in term of media and 100% in term of subject matter. The percentage showed that both media and material from the interactive CD were categorized as very good. The result of questionnaire about studentsâ response to the interactive CD was at 89.16% on small-scale product trial and 91.4% on large-scale product trial with very good criteria. Both results on studentsâ response questionnaire showed that the interactive CD gained positive response from the students. Meanwhile, the data about interactive CD effectiveness was analyzed using T-test. The result of the T-test obtained from SPSS assisted calculation indicated that there was significant influence of interactive CD on the average score of tenth grade students descriptive text. Overall, it can be concluded that the interactive CD is eligible and effective to be used as a learning media in school.